Modal Intelektual dan Daya Saing Perguruan Tinggi di Indonesia - Amrih Rahayuningtyas, Dwi Prihatni; Triana, Eka (Universitas Muhammadiyah Yogyakarta, Indonesia, 2017)
This study aims to examine the factors that affect the disclosure of intellectual capital on universities in Indonesia, and how the influence of intellectual capital disclosures on the competitiveness of higher education internationally. This study uses 35 samples both public and privatemuniversities in Indonesia. This research use linear regression and two stage least square to test the hyphoteses that processed by Eviews.6. The results showed that the autonomy of the universities and colleges rank previously have a significant impact on the disclosure of intellectual capital on the official website of the universities. In addition, the disclosure of intellectual capital have a significant impact on the competitiveness of universities.